1969
DOI: 10.1029/wr005i002p00350
|View full text |Cite
|
Sign up to set email alerts
|

The demand for water: Some empirical evidence on consumers' Response to a commodity uncertain in supply

Abstract: Based on a theoretical model that studies how individuals respond to a commodity uncertain in supply, this paper estimates some demand functions for water in situations where supplies are known to be stochastic. The model is applied to data consisting of a sample of Massachusetts towns, separate functions being estimated for household and in-dustriM demand. Two cross sections are estimated, one for 1962 and one for 1965, the beginning and the end, respectively, of the New England drought.As far as household de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…More functional approach identifies water demand by end-use than by customer class (Bell and Griffin 2008). In this respect, the most usual functional forms used are the linear (García-Valiñas 2005a;Turnovsky 1969), the Cobb-Douglas (DeRooy 1974;Renzetti 1993;Ziegler and Bell 1984) and flexible functional forms such as the translogarithmic (Babin et al 1982;Dupont and Renzetti 2001;Féres and Reynaud 2005;Grebenstein and Field 1979;Renzetti 1992;Reynaud 2003).…”
Section: The Water Demand Of Industry and Of Services: A Brief Revisimentioning
confidence: 99%
See 2 more Smart Citations
“…More functional approach identifies water demand by end-use than by customer class (Bell and Griffin 2008). In this respect, the most usual functional forms used are the linear (García-Valiñas 2005a;Turnovsky 1969), the Cobb-Douglas (DeRooy 1974;Renzetti 1993;Ziegler and Bell 1984) and flexible functional forms such as the translogarithmic (Babin et al 1982;Dupont and Renzetti 2001;Féres and Reynaud 2005;Grebenstein and Field 1979;Renzetti 1992;Reynaud 2003).…”
Section: The Water Demand Of Industry and Of Services: A Brief Revisimentioning
confidence: 99%
“…A review of the analytical and methodological issues of these studies allows us to distinguish two basic approaches: single-equation models, either to jointly estimate the water demand of industry and services (Rees 1969;Turnovsky 1969;Ziegler and Bell 1984) or proposing separate equations for industry and services (Malla and Gopalakrishnan 1999;Williams and Suh 1986), and demand-system models to estimate the demand for different inputs implied in the productive process (Dupont and Renzetti 2001;Féres and Reynaud 2005;Renzetti 1992;Reynaud 2003). In the case of services and industries, water is commonly treated as one more input to consider in the production function.…”
Section: The Water Demand Of Industry and Of Services: A Brief Revisimentioning
confidence: 99%
See 1 more Smart Citation
“…However, IWD studies have been very limited because of the difficulty in gathering internal data and the complicated nature of industrial processes. In conventional economic studies, industrial water demand is derived from optimization behavior of firms (Turnovsky, 1969;DeRooy, 1974). The cost function is generally approximated by either a Cobb-Douglas form (Ziegler and Bell, 1984;Renzetti, 1988) or a Translog form (Grebenstein and Field, 1979;Renzetti, 1992;Reynaud, 2003).…”
Section: Previous Researchmentioning
confidence: 99%
“…Using models similar to those developed in this District's study, these researchers estimated elasticities of 0.7 for western region outdoor use and 0.231 for domestic use (Howe and Linaweaver, 1967). Turnovsky found price elasticities of between 0.05 and 0.40 for the total residential consumption of 19 Massachusetts towns (Turnovsky, 1969). Wong, using data similar to that used in the current District study (pooled cross-sectional), found price elasticities between 0.02 to 0.28 in the Chicago area (Wong, 1972).…”
Section: Hypothesesmentioning
confidence: 99%